THE USE OF PEER FEEDBACK IN INCREASING STUDENTS' DESCRIPTIVE WRITING SKILL - Marianti, Listya (2015)
This research aims to investigate whether or not peer feedback increases students' descriptive writing skill and to find out the responses of the students toward the implementation of peer feedback technique. It employed a quasi experimental design, involving two classes consisting 70 second graders at one of Junior High Schools in Subang. The data were gathered from pre-test, post-test, and questionnaires. The obtained data were analyzed based on The Wechsler Objective Language Dimension (WOLD) proposed by Wechsler (2005). The result of statistical computation showed that peer feedback technique increases students' descriptive writing skill (tobt 2.554 > tcrit 2.000). Furthermore, most of the students positively responded toward the implementation of peer feedback. In conlusion, peer feedback technique is able to increase students' writing skill, especially in descriptive writing. However, to make an effective peer feedback process, it is important to pay attention on the intensive training which is given to the students before applying the peer feedback technique. Keywords: writing, feedback, peer feedback